قصيدة ''يوغرطا'' والوعي السياسي لدى رامبو - لوصيف, عثمان (قــــــراءات, 2019)
تحاول هذه الدراسة ان تسلط الضوء على واحد من أشهر الشعراء العالميين الكبار الذين تركوا تأثيرا قويا في الشعر المعاصر سيما قصيدة النثر، إنه العبقري الفرنسي الشاب آرثر رامبو. لقد اخترنا قصيدة "يوغرطا" لارتباطها الحميم بالوجدان الجزائري موضوعا لدراستنا المؤسسة في المقام الأول على نظرية القراءة والتأويل، وبينا أن رامبو منذ مراهقته المبكرة كان يمتلك وعيا سياسيا عميقا ببعده الإنساني النبيل، لذلك وقف ضد الاحتلال الفرنسي للجزائر رغم وجود أبيه ضابطا برتبة نقيب في الجيش الاستعماري ببلادنا. في هذه القصيدة ينزلق رامبو بالعنوان إلى معاصره الأمير عبد القادر، مؤسس الدولة الجزائرية الحديثة، الذي قاد المقاومة الشعبية الكبرى ضد الاستعمار الفرنسي، مشبها إياه بالبطل النوميدي الشهير يوغرطا الذي قاوم بدوره الاحتلال الروماني للجزائر، هكذا يعيد التاريخ نفسه. قمنا في البداية بعرض سريع لبعض القصائد السياسية، للشاعر، ثم حاولنا مقاربة قصيدة "يوغرطا"؛ فهي نص شعري بالغ الروعة كتب باللاتينية في الأصل ويتألف من ثلاثة وثمانين بيتا مع لازمة أساسية تتكرر خمس مرات، بالإضافة إلى اعتماد العناصر المسرحية كالمشاهد والشخصيات والحوار وغير ذلك.    Abstract: Our study attempts to shed light on one of the most famous universal poets who left a great influence on modern poetry especially the  prosaic poem, throughout all the world, it is the young genius frensh poet Arthur Rimbaud. We have chosen his poem "Jugurtha"as a subject for our analysis which is based on the theory of reading and interpretation. Our study has shown that Rimbaud since his early adolescence possessed a deep consciousness with a human sensation, so he was against the Frensh conquest of Algeria when his father was a captain  in the  colonial army in our country. Rimbaud glorifies in this poem the resistance of the greatest leader El' Amir Abdelkader the founder of the modern Algerian state, comparing him with the great Numidian hero Jugurtha who has resisted the Roman conquest, thus history repeats itself.      At first we have exposed a quick conclusion of some political poems of the poet, then we have tried to approach "Jugurtha" poem; it is a very excellent poetic text written in Latin  and consists of eighty three verses with an essential refrain which repeats five times, besides that the use of the theatric elements as scenes, personages and dialogue.